Pattern of Occurrence of Leukemia at a Teaching Hospital in Eastern Region of Nepal - A Six Year Study - Kulshrestha, Ritu; Sah, SP (Journal of Nepal Medical Association, 2009)
INTRODUCTION:Pattern of leukemia is known to vary widely throughout the world. The characterization of distribution patterns of different subtypes of leukemia in Nepal needs further study. We wanted to study the leukemia pattern in our institute.METHODS:A retrospective study of 196 cases of leukemia, diagnosed at BPKIHS, between January 1997 to December 2002 was done. We analyzed the pattern of leukemia at BPKIHS by morphological subtype, gender, age at diagnosis, time period of diagnosis (seasonality), and geographic distribution.RESULTS:Morphological sub typing showed that 121 cases were of acute leukemia and 75 of chronic leukemia. Chronic myeloid leukemia constituted the single largest group comprising 35.2 % of all cases, followed by acute myeloid leukemia (28.57 %) and acute lymphoid leukemia (19.9 %). Maximum numbers of cases were from the lowlands while least number of cases were from the mountain districts. Results were compared with literature from Nepal and other countries. This is the second series of leukemia from Nepal.CONCLUSIONS:The data published in this study reflects the leukemia pattern in the eastern region of Nepal. The pattern and distribution of AML, CML, ALL was similar to that in the developed western countries while the lesser frequency of CLL was similar to that in Southeast Asian regionKey Words:leukemia, pattern, eastern Nepal, seasonality.